2021
DOI: 10.33541/jet.v7i3.2921
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Strategies Toward Real-Time Online Teaching at an Informal English Institution: An Explanatory Study on Instructional Strategies

Abstract: Studies on teachers’ self-regulation are abundant and still posit strategic relevance for teacher professional development. Nevertheless, such studies focusing on online learning are yet underrepresented within informal education contexts. Hence, this study aimed to investigate the teachers’ self-regulation in implementing the instructional strategies in real-time online teaching. This study was undertaken in an English course in an informal institution during the COVID-19 pandemic. Using the explanatory seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Project-based learning and other forms of active student learning have the potential to provide students with rich opportunities to practice (Dean et al, 2023). The fi ndings of the study of Noviani (2021) demonstrated that the role of teacher's self-regulation in teaching and implementing instructional strategies is essential in realtime online teaching. This concludes that the higher the self-regulation, the better it is for the mastery of instructional strategies and the positive output of realtime online teaching.…”
Section: Instructional Practicesmentioning
confidence: 99%
“…Project-based learning and other forms of active student learning have the potential to provide students with rich opportunities to practice (Dean et al, 2023). The fi ndings of the study of Noviani (2021) demonstrated that the role of teacher's self-regulation in teaching and implementing instructional strategies is essential in realtime online teaching. This concludes that the higher the self-regulation, the better it is for the mastery of instructional strategies and the positive output of realtime online teaching.…”
Section: Instructional Practicesmentioning
confidence: 99%